Generation of system-wide parameters for Falcon cryptosystem for 256, 384, 512 bits of security - Горбенко, І.Д.; Кандій, С.О.; Єсіна, М.В.; Острянська, Є.В. (Radiotekhnika, 2020)
Globally, the efforts of a significant number of crypto-theorists, mathematicians and cryptologists-practitioners are focused on the NIST PQC open competition. One of the main tasks of the competition consists in development and adoption of a post-quantum ES standard or standards. The finalists of the second stage of the NIST competition were three ES mechanisms – CRYSTALS-DILITHIUM, Falcon and Rainbow. In addition, three alternative candidates were identified that require more detailed research. In general, a comprehensive analysis of the finalists is an important task for cryptologists in the global cryptocommunity. Moreover, security, i.e. brining the cryptographic stability of two finalist candidates, to the ES standard – CRYSTALS-DILITHIUM and Falcon, is based on problems in the theory and practice of algebraic lattices. Studies show that among the ES schemes on lattices it differs slightly from other candidates and has prospects for the adoption as the Falcon algorithm standard. The main and dominant approach to the design of the Falcon ES mechanism is the use of the Fiat-Shamir transformation with interruptions. The sets of system-wide parameters that ensure resistance to all known and potential attacks should be found for the safe use of the Falcon ES. In the process of forming the requirements for ES within the competition, the NIST was interested only in sets of system-wide parameters up to 256 bits of classical security inclusive. However, according to the authors of this work, in the future it is advisable to provide at least 384 and 512 bits of security for classical cryptanalysis and at least 192 and 256 bits of security for quantum cryptanalysis. The article briefly considers the essence of the Falcon electronic signature (ES) algorithm. An analysis of possible attacks on the algorithm and the mechanisms of their implementation is also performed. The process of generating system-wide parameters for 256, 384, 512 stability bits is considered. Conclusions and recommendations are given. The objective of the work is the classification and initial analysis of known attacks on the ES Falcon cryptosystem, setting limits and developing practical algorithms for calculating (generating) system-wide parameters to provide not less than 256, 384 and 512 security bits for classical and not less than 128, 192 and 256 security bits for quantum cryptanalysis.